2002
DOI: 10.1124/jpet.102.034785
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Latently Expressed CYP2C11, CYP3A2, and Growth Hormone Defects in Neonatally Monosodium Glutamate-Treated Male Rats by theN-Methyl-d-Aspartate Receptor Antagonist Dizocilpine Maleate

Abstract: Neonatal administration of monosodium glutamate (MSG) can produce latently expressed defects in drug metabolism and growth hormone secretion as well as stunted growth and obesity. Instead of secreting growth hormone in the masculine episodic profile, plasma hormone levels are generally undetectable in affected adult male rats. Moreover, male-specific isoforms of cytochrome P450 (P450; e.g., CYP2C11 and CYP3A2), whose combined levels comprise the bulk of the total hepatic P450 in adult male rats, are similarly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 26 publications
0
19
0
4
Order By: Relevance
“…After repeated high doses of MSG, mice become obese in adulthood, as attested by increased Lee index and adipocyte hypertrophy (Fabres-Machado and Saito, 1995;Dolnikoff et al, 2001). These animals also present several neuroendocrine dysfunctions as decreased growth hormone secretion and hyperinsulinaemia (Nemeroff et al, 1978;Scallet and Olney, 1986;Maiter et al, 1991;Fabres-Machado and Saito, 1995;Kaufhold et al, 2002), without hyperphagia (Bunyan et al, 1976). On the other hand animals with electrolytic lesion in the ventromedial hypothalamus (VMH) are obese being hyperphagic (Baile et al, 1970;Bray et al, 1981) but obesity can occur even without increase in food intake (Han and Frohman, 1970).…”
Section: Introductionmentioning
confidence: 94%
“…After repeated high doses of MSG, mice become obese in adulthood, as attested by increased Lee index and adipocyte hypertrophy (Fabres-Machado and Saito, 1995;Dolnikoff et al, 2001). These animals also present several neuroendocrine dysfunctions as decreased growth hormone secretion and hyperinsulinaemia (Nemeroff et al, 1978;Scallet and Olney, 1986;Maiter et al, 1991;Fabres-Machado and Saito, 1995;Kaufhold et al, 2002), without hyperphagia (Bunyan et al, 1976). On the other hand animals with electrolytic lesion in the ventromedial hypothalamus (VMH) are obese being hyperphagic (Baile et al, 1970;Bray et al, 1981) but obesity can occur even without increase in food intake (Han and Frohman, 1970).…”
Section: Introductionmentioning
confidence: 94%
“…The authors showed increases in GLU levels and activation of GLU-receptors after neonatal s.c. administration of MSG at doses of 4 mg/g body weight and an increase in glial cell reactivity and important changes in NMDA-R molecular composition, with signs of neuronal damage. Kaufhold et al (2002) were able to prevent the adverse effects of neonatal MSG treatment by concurrent administration of a selective and highly potent noncompetitive NMDA-R antagonist of GLU.…”
Section: Introductionmentioning
confidence: 99%
“…On the 22nd day, the animals were weaned and the female was removed from the cage. On the 90th day, obesity was evaluated by Lee index, calculated by body mass (g) 0.33 /naso-anal length (cm) (Nakagawa et al 2000, Kaufhold et al 2002. Thus, obese (MSG) animals were selected from i-MSG group by Lee index O0.300 and the i-control rats were subdivided into two groups: control (Lee index %0.300) and FD control (control animals fasted for 72 h).…”
Section: Animals and Treatmentsmentioning
confidence: 99%